DISSIMILATORY SULFATE REDUCTION BY VARIOUS DESULFOVIBRIO SP. STRAINS OF THE HUMAN INTESTINE - I. В. Кушкевич (Mìkrobìologìâ ì Bìotehnologìâ. Мікробіологія і біотехнологія, 2013)
The aim of this research was to study the dissimilatory sulfate reduction process by various Desulfovibrio sp. strains of the human intestine, such as bacterial growth, sulfate- and lactate usage, production of sulfide and acetate by the strains, and carry out cluster and correlation analyses of this process. Methods. Microbiology methods of the study for bacterial strains cultivation and photometric methods for determination of bacterial biomass and hydrogen sulfide concentration were used, sulfate ions concentration was determined by turbidymetric method, lactate concentration was carried out by lactate dehydrogenase. Acetate ions accumulation by the strains was determined by titration. Using the experimental data, the methods of statistical analysis have been also used. Results. The various Desulfovibrio sp. strains accumulated different biomass for ten days of cultivation in modified Kravtsov-Sorokin’s medium. The highest biomass (up to 3.89 g/l) was accumulated by Desulfovibrio sp. strain Vib-7 on the sixth day of cultivation. Clustering of bacterial growth parameters has showed the greatest similarity between strains Desulfovibrio sp. strain Vib-7 and Desulfovibrio sp. strain Vib-9. After using all of the sulfate and lactate from the medium, the bacteria stopped growing and the stationary growth phase began. Clustering of the parameters of sulfate usage has showed that strains Desulfovibrio sp. Vib-1 and Desulfovibrio sp. Vib-2 were combined in one cluster, and the strains Desulfovibrio sp. Vib-7 and Desulfovibrio sp. Vib-9 were in another cluster. The strong correlation between all parameters of dissimilatory sulfate reduction (growth, reduction of sulfate, accumulation of sulfide, use of lactate and accumulation of acetate) by the Desulfovibrio sp. strains has been determined. Thus, the obtained results may be promising for further study, in particular for creating ulcerative colitis models, prediction and prevention of human inflammatory bowel disease.